Thrombin Generation in Newborn Plasma Is Critically Dependent on the Concentration of Prothrombin - Andrew, Maureen; Schmidt, Barbara; Mitchell, Lesley; Paes, Bosco; Ofosu, Frederick (Thrombosis and Haemostasis, 1990)
The ability to generate thrombin is decreased and delayed in plasma from the healthy newborn infant compared to the adult. Only 30 to 50% of peak adult thrombin activity can be produced in neonatal plasma. To test whether this observation can be explained by the low neonatal levels of the contact or vitamin K dependent factors, we measured neonatal thrombin generation after raising the concentration of these factors to adult values. We also determined whether the addition of a variety of blood products to neonatal plasma improved thrombin generation. An amidolytic method was used to quantitate intrinsic (APTT) and extrinsic (PT) pathway thrombin generation in defibrinated pooled cord plasma from healthy term infants. Added individually, factors VII, IX, X or the contact factors (CF) failed to alter the rate or the total amount of thrombin generated in neonatal plasma. In contrast, the addition of prothrombin increased the total amount of thrombin generated to above adult values in both the APTT and the PT systems but did not alter the rate of thrombin generation. The rate of thrombin generation in cord plasma shortened after a combination of II, IX, X and CF was added to the APTT system or II, VII and X to the PT system. In both systems, the total amount of thrombin generated was linearly related to the initial prothrombin concentration. Each of fresh frozen plasma, cryoprecipitate, plasma from platelet concentrates, or factor IX concentrate (in amounts used therapeutically) caused an increase in the total amount of thrombin generated which was related to the increase in prothrombin concentration. Thus, the total amount of thrombin generated in newborn plasma is critically dependent on the prothrombin concentration whereas the rate at which thrombin is generated is dependent on the levels of many other coagulation proteins in combination.
Keywords: Coagulation; Prothrombin; Newborn